3D printable concrete with natural and recycled coarse aggregates: Rheological, mechanical and shrinkage behaviour. (January 2022) - Rahul, A.V.; Mohan, Manu K.; De Schutter, Geert; Van Tittelboom, Kim
Abstract: In the current study, we examine the effect of using natural and recycled coarse aggregates in designing 3D printable concrete. We assessed the rheological behaviourusing a dynamic shear rheometer, and it was observed that the addition of coarse aggregates significantly decreased the yield stress and marginally lowered the plastic viscosity. This was attributed to the increase in the paste and water film thickness with the addition of larger aggregates. Therefore, a reduction in the superplasticizer dosage is required to obtain coarse aggregate mixtures with similar yield stress and buildability to the control mixture. The mechanical properties were evaluated by using beam and cube samples cut out from printed wall elements. A marginal decrease in compression and flexural strength was observed for both the mixtures with natural and recycled coarse aggregates. The total and autogenous shrinkage assessment was performed using mould cast prismatic specimens, while the shrinkage cracking potential was evaluated using the restrained ring test. The coarse aggregate mixtures showed lower total and autogenous shrinkage. Notably, the addition of the saturated recycled aggregates significantly lowered the autogenous shrinkage, possibly due to internal curing. As a result, a relatively lower strain rate factor and slower development of tensile stresses occurred in the restrained shrinkage test, increasing the cracking age for the coarse aggregate mixtures. The current study, therefore, shows good potential for using natural and recycled coarse aggregates in 3D printable concrete.